2023
DOI: 10.1088/1748-3190/acb521
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of the sweepback angle effect on the thrust generation of a robotic penguin wing

Abstract: Penguins have evolved excellent swimming skills as diving birds, benefiting from their agile wings. This paper experimentally analyses the effect of the wing sweepback angle on thrust generation using a robotic penguin wing. A developed wing mechanism that can realize penguin-like flapping and feathering motion was employed for actuating five alternative wing models with different sweepback angles from 0° to 50°. Force measurements under a steady water flow were conducted for both fixed and flapping states for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…On this basis, we performed 3-D motion measurements on a real penguin and revealed quantitative 3-D wing kinematics [16]. As a result, it was found that the basic wing kinematics relative to the body mainly consists of obliquely straight flapping with spanwise feathering, while sweeping motion was found to have little impact on thrust [17]. The flapping motion and the feathering motion follow sinusoidal curves and the phase of feathering motion lags behind that of flapping motion by π/2 [18].…”
Section: Introductionmentioning
confidence: 99%
“…On this basis, we performed 3-D motion measurements on a real penguin and revealed quantitative 3-D wing kinematics [16]. As a result, it was found that the basic wing kinematics relative to the body mainly consists of obliquely straight flapping with spanwise feathering, while sweeping motion was found to have little impact on thrust [17]. The flapping motion and the feathering motion follow sinusoidal curves and the phase of feathering motion lags behind that of flapping motion by π/2 [18].…”
Section: Introductionmentioning
confidence: 99%